(untitled) (Economics Studies and Banking Journal (DEMAND), 2024)
This research aims to analyze the influence of risk, management quality, company size and bank liquidity on banking financial performance in the 2018-2022 period. This research uses multiple linear regression analysis methods on a sample of 20 banks selected purposively. Data was collected from banks’ annual financial reports involving credit risk (NPL) , efficiency ratios (BOPO), company size (Ln total assets), liquidity ratios (LDR) and financial performance ratio (ROA) . The analysis results show that risk, especially credit risk, has a significant negative impact on financial performance. In contrast, management quality has a significant positive impact on financial performance. However, firm size and bank liquidity, although they have a positive impact on financial performance, are not significant in the context of this study. These findings provide insight into the factors that banks need to pay attention to to improve financial performance.